Cultural tourism: new opportunities for diversifying the tourism industry in Botswana - Saarinen, Jarkko; Moswete, Naomi; Monare, Masego J. (Bulletin of Geography. Socio-economic Series, 2014)
Botswana is known as a wilderness and safari-tourism destination, which attracts high-end overseas visitors to the country. Since the 1990s the country’s tourism policy has been based on a so called ‘High Value – Low Volume’ (HVLV) strategy referring to the aim of attracting limited numbers of tourists with high expenditure patterns. However, while such tourism operations have contributed to the Gross Domestic Product (GDP) of the country and offered investment opportunities for international companies, the position of Botswana as a HVLV destination is increasingly criticised. It is seen as offering too narrow prospects for the growth of the industry and for the local participation and benefit sharing in tourism in future. Hence, there is a need for diversification of the product with deeper involvement of local people to tourism. Therefore, communities and Botswana’s cultural and heritage attractions are increasingly seen as one of the future cornerstones of tourism development. This paper provides an overview of cultural tourism with specific reference to existing cultural and heritage attractions and the potential thereof for tourism in Botswana. The paper concludes that while the role of culture is still underutilised in tourism, the cultural tourism in Botswana has the potential to contribute to a more equitable distribution of tourism-based development and the related benefits for local communities.